Sternal osteomyelitis caused by Aspergillus fumigatus years after coronary artery bypass grafting: A case report. (2022) - Hingtgen, Austin; Aggarwal, Rishav; Avilala, Shreya; Mohammed, Azmath; Kelly, Rosemary
Abstract: Sternal infection after cardiac surgery is an infrequent post-operative complication. Aspergillus sternal osteomyelitis is a rarity. We review the case of a 77-year-old man with invasive aspergillosis of the sternum and left costal cartilage 23 years after undergoing cardiac surgery. The patient promptly underwent surgical irrigation and debridement, followed by antifungal therapy. Clinical suspicion of sternal fungal infection should be high in patients with mediastinitis with a history of cardiac surgery. Treatment should be prompt. Highlights: Aspergillus sternal osteomyelitis is a rare complication after median sternotomy. Invasive aspergillosis rarely causes osteomyelitis several years after sternotomy. Treatment for sternal osteomyelitis should begin upon suspicion of infection. Irrigation and debridement are necessary for sternal osteomyelitis treatment. Voriconazole therapy is effective for non-resistant Aspergillus osteomyelitis.